What office‐based interventions are effective for treating abnormal glucose levels or preventing progression to type 2 diabetes?. Issue 8 (August 2017) - Moss, David; Cieslak, Daniel
Abstract : EVIDENCE‐BASED ANSWER : Telemedicine interventions—including telephone and Internet‐based monitoring and education—result in a slight reduction in glycated hemoglobin (HbA1C) in patients with diabetes (SOR: C, meta‐analysis of RCTs with disease‐oriented outcomes). In patients at risk for diabetes, an intensive lifestyle‐based intervention that includes case managers, education, and other individualized forms of support reduces the incidence of diabetes by 58% over 3 years (with continued but less effect over 15 years), reduces the prevalence of microvascular disease among women, and is superior to metformin alone (SOR: B, RCT and large cohort study).